Dynamic damping of dislocations in the irradiated LiF crystals - Petchenko, G.A. (Functional Materials, 2012)
To study the nature of the mechanisms that limit the viscous motion of dislocations, the dampfed dislocation resonance in LiF crystals at room temperature in the range of radiation doses of 0-1000 R has been scrutinized by the impulse echo method in the frequency range 37.5-232.5 MHz. From the frequency curves, taken from crystals with different doses of radiation, the dependencies of the viscosity coefficient B and the average effective length of the dislocation segment L from the time of irradiation has been determined. On the basis of the carried out measurements, calculations and analysis it has been concluded that the dynamic damping of dislocations in the given object, and given experimental conditions is determined only by the phonon spectrum of the crystal.